PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS MODEL KONTEKSTUAL PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SD - Suryani, Ade Irma (LP2M Universitas Adzkia, 2023)
ABSTRACT This research is motivated by the problem that the media used by educators as a teaching medium tends to use pictures in theme books, educators do not use existing facilities at school such as infocus as a tool for using video media. This study aims to determine the validity and practicality of audio-visual media based on contextual models in integrated thematic learning in grade IV of elementary school. This type of research is research and development (Research and Development). The development model used is the 4-D model which consists of the define stage, the design stage, the development stage, and the dissemination stage. The practical instrument is in the form of a questionnaire of educators and students. Based on the results in the field , researchers get overall validation results with an average of 84.53% with a very valid category, the practicality of educators gets an average score of 91.99% with a very practical category and the practicality of students gets an average score of 94.50 % with very practical category. Keywords: Contextual Model-Based Audio Visual Media, Validity and Practicality